Ethnomathematics Exploration: Offering Dance Performance (Makan Sirih) Ethnic Malay Deli North Sumatra - Hasibuan, Aulia Rahman; Br Ginting, Siti Salamah (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
The purpose of this research is to explore a relationship between applied mathematics and a culture called ethnomathematics. The culture that will be used as the research topic is the performance culture of the Offering Dance (Makan Sirih) from the Deli Malay ethnic group in North Sumatra. This study is a research that uses descriptive qualitative research methods using an ethnographic approach that analyzes and describes a local culture based on facts obtained in the field. From the results of this research, it is revealed that, in the performance of the Offering Dance (Makan Sirih) in the Malay ethnic Deli of North Sumatra, there are various applications of mathematical concepts such as the concept of sets, counting, functions, and flat shapes. This can lead to new breakthroughs that underlie the formation of new mathematics learning designs for educational institutions. Along with this, this research also aims to improve the public's view of mathematics, that mathematics is a science that also has connections with all forms of activities in daily life.